2014
DOI: 10.1111/1751-7915.12186
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation by enteric pathogens and its role in plant colonization and persistence

Abstract: The significant increase in foodborne outbreaks caused by contaminated fresh produce, such as alfalfa sprouts, lettuce, melons, tomatoes and spinach, during the last 30 years stimulated investigation of the mechanisms of persistence of human pathogens on plants. Emerging evidence suggests that Salmonella enterica and Escherichia coli, which cause the vast majority of fresh produce outbreaks, are able to adhere to and to form biofilms on plants leading to persistence and resistance to disinfection treatments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(156 citation statements)
references
References 175 publications
2
144
0
Order By: Relevance
“…This work adds to increasing evidence, such as molecular fingerprinting of E. coli in water and crops (Forslund et al, 2012), showing that irrigation with TWW may hold promise from a microbial pathogen standpoint. Controlled studies have shown that pathogens could invade the roots from the soil and colonize plants ( Barak and Liang, 2008;Barak et al, 2011;Yaron and Römling, 2014), yet the high bacterial counts introduced in these studies (10 7 -10 9 ) were never encountered in the TWW or soil in the present study (Table 2). Thus, further analyses should be conducted by agronomists and public health officials aiming of test the irrigation of TWW on a brad array of soil types and vegetables.…”
Section: Discussionmentioning
confidence: 51%
“…This work adds to increasing evidence, such as molecular fingerprinting of E. coli in water and crops (Forslund et al, 2012), showing that irrigation with TWW may hold promise from a microbial pathogen standpoint. Controlled studies have shown that pathogens could invade the roots from the soil and colonize plants ( Barak and Liang, 2008;Barak et al, 2011;Yaron and Römling, 2014), yet the high bacterial counts introduced in these studies (10 7 -10 9 ) were never encountered in the TWW or soil in the present study (Table 2). Thus, further analyses should be conducted by agronomists and public health officials aiming of test the irrigation of TWW on a brad array of soil types and vegetables.…”
Section: Discussionmentioning
confidence: 51%
“…However, despite the increased awareness of food safety issues, the occurrence of foodborne disease outbreaks related to these products is constantly increasing (Gilbert & McBain, 2003;Ölmez & Kretzschmar, 2009;Vitale & Schillaci, 2016) with several pathogenic bacteria associated, such as Listeria monocytogenes, Clostridium botulinum, Bacillus cereus, Escherichia coli O157:H7 and Salmonella spp. (Olaimat & Holley, 2012;Seiber, 2012;Warriner, Huber, Namvar, Fan, & Dunfield, 2009), as well as viruses (norovirus and hepatitis A) and protozoa (Cryptosporidium parvum) (Berger, Sodha, Shaw, Griffin, Pink, Hand, & Frankel, 2010;Yaron & Romling, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…are the two microorganisms linked to the largest foodborne outbreaks and consequent human infections (Warriner et al, 2009;Yaron & Romling, 2014). a 2.58 log CFU/cm 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Persistence in well water after 7 days was 3.3 Ϯ 0.3 log CFU/ml for 14028 and 3.8 Ϯ 0.5 log CFU/ml for MHM112. ness of a surrogate (17), since biofilms facilitate environmental persistence (38). Therefore, biofilm formation on polystyrene and polypropylene was examined for the surrogate strain and the wild type, as well as for individual mutants.…”
Section: Resultsmentioning
confidence: 99%